Vessel wall MR imaging of aortic arch, cervical carotid and intracranial arteries in patients with embolic stroke of undetermined source: A narrative review - Sakai, Yu; Lehman, Vance T.; Eisenmenger, Laura B.; Obusez, Emmanuel C.; Kharal, G. Abbas; Xiao, Jiayu; Wang, Grace J.; Fan, Zhaoyang; Cucchiara, Brett L.; Song, Jae W. (Frontiers in Neurology, 2022)
Despite advancements in multi-modal imaging techniques, a substantial portion of ischemic stroke patients today remain without a diagnosed etiology after conventional workup. Based on existing diagnostic criteria, these ischemic stroke patients are subcategorized into having cryptogenic stroke (CS) or embolic stroke of undetermined source (ESUS). There is growing evidence that in these patients, non-cardiogenic embolic sources, in particular non-stenosing atherosclerotic plaque, may have significant contributory roles in their ischemic strokes. Recent advancements in vessel wall MRI (VW-MRI) have enabled imaging of vessel walls beyond the degree of luminal stenosis, and allows further characterization of atherosclerotic plaque components. Using this imaging technique, we are able to identify potential imaging biomarkers of vulnerable atherosclerotic plaques such as intraplaque hemorrhage, lipid rich necrotic core, and thin or ruptured fibrous caps. This review focuses on the existing evidence on the advantages of utilizing VW-MRI in ischemic stroke patients to identify culprit plaques in key anatomical areas, namely the cervical carotid arteries, intracranial arteries, and the aortic arch. For each anatomical area, the literature on potential imaging biomarkers of vulnerable plaques on VW-MRI as well as the VW-MRI literature in ESUS and CS patients are reviewed. Future directions on further elucidating ESUS and CS by the use of VW-MRI as well as exciting emerging techniques are reviewed.